2020
DOI: 10.1001/jamasurg.2020.0422
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Contribution of the Work Relative Value Unit Scale to Differences in Physician Compensation Across Medical and Surgical Specialties

Abstract: IMPORTANCEThe work relative value units (wRVUs) for a physician service can be conceptualized as the amount of time spent by the physician multiplied by a compensation rate (wRVUs/min). Disproportionately high compensation rates assigned to procedures have been blamed for pay differences across specialties, but to our knowledge, a comprehensive assessment is lacking.OBJECTIVE To assess how compensation rates built into work RVUs contribute to differences in physician compensation across specialties.DESIGN, SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 16 publications
2
39
0
Order By: Relevance
“…The findings also align with UK research that found that a proposed new contract payment structure could lead to the pay rise for junior doctors with the most onerous shifts but did not provide much financial compensation for junior doctors who work every other weekend [25]. Third, the pay of medical personnel was strongly associated with the average salary of an urban worker and the hospital type, and the worker's gender, age, education status, work characteristics, position, professional titles, seniority and departments, which is consistent with previous studies [26].…”
Section: Discussionsupporting
confidence: 85%
“…The findings also align with UK research that found that a proposed new contract payment structure could lead to the pay rise for junior doctors with the most onerous shifts but did not provide much financial compensation for junior doctors who work every other weekend [25]. Third, the pay of medical personnel was strongly associated with the average salary of an urban worker and the hospital type, and the worker's gender, age, education status, work characteristics, position, professional titles, seniority and departments, which is consistent with previous studies [26].…”
Section: Discussionsupporting
confidence: 85%
“…The American Medical Association's RUC meets three times per year to review survey results from physicians to determine the RVUs for each CPT code that physicians bill for. This, in turn, determines the amount a provider will be reimbursed based on the anticipated time, risk, mental and physical effort required for care 4,5 . Secondary to the subjective nature of quantifying these categories, this is subject to inherent variability, particularly when members of the RUC disproportionately belong to procedure‐based specialties 4–6 .…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, determines the amount a provider will be reimbursed based on the anticipated time, risk, mental and physical effort required for care. 4,5 Secondary to the subjective nature of quantifying these categories, this is subject to inherent variability, particularly when members of the RUC disproportionately belong to procedure-based specialties. [4][5][6] The RVU system is prone to implicit bias and may force facilities to use the chargemaster prices to correct for this, potentially leading to significant variability in the MUR of certain procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated these rates using the building block method (Supporting Figure). 3,7,10 This previously established method divides physician work into four non-overlapping blocks: 1) pre-service work, including pre-operative evaluation, dressing/scrubbing/ waiting, and patient positioning; 2) intraservice work from incision to closure (i.e., "skin-to-skin" time); 3) immediate post-service work (e.g., patient care in the post-operative recovery room); and 4) global period work (as applicable), such as inpatient rounding and outpatient clinic visits following surgery (Fig. 1).…”
Section: Compensation Rate Calculationmentioning
confidence: 99%